Study of Pathophysiological Effects of the Nematode Parasite Eustrongylides sp. on Freshwater Fish Channa punctatus by Hematology, Serum Biochemical, and Histological Studies - Kundu, Ivy; Bandyopadhyay, Probir Kumar; Mandal, Dipak Ranjan; Gürelli, Gözde (Galenos Yayinevi, 2016)
The aim of this study was to study the pathophysiological effects on Channa punctatus due to the nematode parasite Eustrongylides sp.A total of 250 fish were examined during the period January 2012-2014. Hematological, serum biochemical, histological, and scanning electron microscopic studies were performed on normal and infected hosts to study the effects caused by the nematode.The mean values of red blood corpuscle [RBC] count, hematocrit, and hemoglobin were significantly higher (P<0.01) in noninfected fish, while the values of white blood corpuscle [WBC] count, mean corpuscular volume [MCV], and mean corpuscular hemoglobin [MCH] were significantly higher (P<0.01) in infected fish. In infected fish, the average values of aspartate amminotransferase [AST] (416 UL-1), alanine amminotransferase [ALT] (73.35 UL-1), alkaline phosphatase [ALP] (161.6 mg dl-1), and cholesterol (154.82 mg dl-1) were significantly higher (P<0.01) than those in noninfected fish. Significant differences were also observed in total protein and glucose levels between the infected and noninfected fish. Histological and scanning electron microscopic studies of the host tissues revealed a series of pathological changes and mechanical damage.It can be concluded that Eustrongylides sp. has a significant impact on its host and thus the parameters outlined in the present paper may be employed as tools in monitoring the health status of fish in culture practices.
Keywords: Erythrocyte Indices; Fish Diseases; Hematocrit; Nematoda; Animals; Fresh Water; Nematode Infections; Perciformes; 14. Life underwater; 3. Good health